Harpalyce brasiliana Benth: A prolific source of bioactive flavonoids with antiophidic potential. (February 2021) - Pontes, Marcela de Castro Nogueira Diniz; Torres-Rêgo, Manoela; de Aquino, Ana Karoline Silva; de Aquino, Nayara Coriolano; Teles, Yanna Carolina Ferreira; Ximenes, Rafael Matos; Monteiro, Helena Serra Azul; Silveira, Edilberto Rocha; Araújo, Renata Mendonça
Graphical abstract: Highlights: Fifteen flavonoids were isolated from roots, leaves and heartwoods of Harpalyce brasiliana . Structures of two new isoflavones were successfully determined by spectroscopic techniques. The cabenegrin A-I I showed antivenom effects against Bothrops jararacussu snake venom. Abstract: Harpalyce brasiliana Benth (Leguminoseae) has been previously described as a prolific source of flavonoids, such as flavonols, isoflavonoids and mainly pterocarpans. This plant has been used in folk medicine and its isolated compounds have been reported for their anti-inflammatory, antitumor and antiophidic properties. This study reports a phytochemical investigation of the leaves, heartwood, and roots of H. brasiliana and evaluates its effect against the Bothrops jararacussu (Bj) envenomation. The isolation of all substances was performed using different chromatographic methods and the structures were elucidated by 1D and 2D NMR, IR and MS analysis. The new isoflavonoids harpalycin II-A (4 ) and harpalycin I-A (9 ) were isolated from the leaves and heartwood, respectively. Thirteen known flavonoids were isolated from leaves, heartwood, and roots. The treatment of rats with cabenegrin A-II (14 ) reversed the biochemical (glucose, aspartate aminotransferase, alanine transaminase, urea, creatinine, uric acid, and creatine kinase) and hematological (erythrocytes, hemoglobin, hematocrit, hemoglobin and platelets) alterations induced by Bj venom. In addition, cabenegrin A-II demonstrated significant inhibition of the hypotensive effect of Bj venom. These data demonstrated the isolation of two new isoflavonoids of species, as well as the promising antiophidic effect of bioactive flavonoids from H. brasiliana .